Creating a Personal Learning Environment through Information Behavior Inspired by Teacher’s Feedback - Janiūnienė, Erika; Stonkienė, Marija; Šupa, Maryja (Information & Media, 2024)
Teacher’s feedback, accompanied by student self-reflection, promotes the integration of learning environments and the creation of a personal learning environment for students. The analysis of both pedagogical and technological discourses of personal learning environments draws attention to the importance of the student’s information behavior in the creation of a personal learning environment.This study examines students’ information behavior, initiated by the teacher’s feedback. An exploratory study (survey, n=111) showed that the teacher’s feedback stimulates self-reflection among the participants and is associated with a clear personalization of some of the study participants’ learning needs. Teacher’s feedback stimulates information seeking. Information behavior inspired by teacher’s feedback builds their personalized learning environment through information seeking and creation of information/learning products. It has been pointed out that consistency of teacher’s feedback is important for information seeking and for making sense of and using information. Teacher’s feedback inspires cooperative information behavior. This demonstrates the importance of students’ social self-reliance, both in the sharing of feedback information and in learning, searching, selecting information resources, and creating information/learning products. At the same time, it demonstrates the objectives, the means of the social dimension of the participants’ personal learning environment. The study of the technological aspects of information behavior showed that technology is most often used for information seeking, information organization and social interaction. The study showed the interactive use of university and external technological platforms.